THE CURRENT STATE OF MONETARY CIRCULATION AND MEASURES TO ENSURE ITS SUSTAINABILITY - Makisheva Zhanna Anatolevna,; Kabdullina Gulmira Kabidenovna,; Shaikenova Nurgul Tynyshtykovna,; Kenges Gulzhihan Kengeskyzy, (Academic Journal of Physical and Chemical Sciences, 2020)
The stability of the monetary system is a backbone factor that reflects the essence of the social process and determines the stability of the development of a market economy and its component - the regional economy. Money is a reproductive category; cash issued by the Bank of Russia as a monopolist in the total mass of reproduction entities serves both the production sphere and the distribution, exchange and consumption spheres. Fuelled by advances in technology and communications, the financial infrastructure has developed into a perpetually operating global system in which "megabyte money" (i.e. money in the form of symbols on computer screens) can move anywhere in the world with speed and ease. Currently, the stability of the monetary system is significantly affected by risks arising from the shortage of the long-term resource base and the transformation of short-term liabilities of banks into long-term investments.